Effectively Improving Capacitive Performance of Three‐Dimensional Iron(III) Oxide Nanotube Arrays by Rationally Filling Mesopores with Polypyrrole. Issue 9 (14th July 2016) - Wang, Zhikui; Pan, Qinmin
Abstract: Fe2 O3 is a promising electrode material for electrochemical capacitors, but challenges remain in enhancing its capacitive performance. Herein, we effectively improved the capacitive properties of 3D Fe2 O3 nanotube arrays by partly filling their mesopores with polypyrrole (PPy) through vapor‐phase polymerization. Although the filled PPy was only 9.7 wt %, the resulting hybrid Fe2 O3 /PPy arrays tripled the specific capacitance to 367 F g −1 at 1.0 A g −1, doubled their high rate capability (106 F g −1 at 10 A g −1 ), and exhibited good cycling stability at high current density. The capacitive performances of the hybrid arrays are among the best for Fe2 O3 ‐based electrodes. It is believed that the partly filled mesopores not only increase the electronic conductivity and electroactivity of each hybrid nanotube but also avoid blocking the ion‐diffusion path. All the features allow the arrays to exhibit synergetic pseudocapacitive properties and to maintain stable and fast electrochemical kinetics. Our findings provide an efficient strategy to boost the electrochemical performances of transition‐metal oxide nanomaterials by rationally filling their mesopores with a small amount of a conductive polymer. Abstract : Fill 'er up ! The capacitive performances of 3D Fe2 O3 nanotube arrays are dramatically improved by partly filling their mesopores with polypyrrole (PPy). Although the filled PPy accounts for only 9.7 wt %, the resulting hybrid Fe2 O3 /PPy arrays triple the specific capacitance and double the rate capability of Fe2 O3 arrays and, furthermore, exhibit good cycling stability at high current density.